2017
DOI: 10.1088/1361-6528/aa9daa
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of well-distributed titania nanopillar arrays on Ti6Al4V surface by induction heating for enhancing osteogenic differentiation of stem cells

Abstract: Great effort has recently been devoted to the preparation of nanoscale surfaces on titanium-based implants to achieve clinically fast osteoinduction and osseointegration, which relies on the unique characteristics of the nanostructure. In this work, we used induction heating treatment (IHT) as a rapid oxidation method to fabricate a porous nanoscale oxide layer on the Ti6Al4V surface for better medical application. Well-distributed vertical nanopillars were yielded by IHT for 20-35 s on the alloy surface. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…As shown in Figure , compared with the control group, the mRNA gene expression level of ALP, Col I, Runx2, and OCN on β-TCP/nanopattern scaffolds were significantly up-regulated, which demonstrated that the scaffolds modified by the nanopattern contributed to the osteogenic differentiation of mBMSCs. The results of our study were consistent with many previous studies, which have shown that nanodots on the surface of bone repair scaffolds promotes stem cell differentiation into osteoblasts through upregulating the osteogenesis-related gene and protein expression levels. The underlying mechanisms may be that the nanodots can activate the Wnt signaling pathway inside cells, which regulated the formation of primary cilium when cells grown on nanodots structure, and regulated the intracellular actin–myosin tension, which in turn modulates the osteogenic differentiation process of cells. Therefore, the nanopattern structures fabricated by our method could be promising topography to enhance bone regeneration, which can be used to fabricate patterns on the surface of bone repair scaffold. However, at present, the application of surface topologies in the field of bone repair is only limited to in vitro cell biology and in vivo animal experimental studies.…”
Section: Resultssupporting
confidence: 89%
“…As shown in Figure , compared with the control group, the mRNA gene expression level of ALP, Col I, Runx2, and OCN on β-TCP/nanopattern scaffolds were significantly up-regulated, which demonstrated that the scaffolds modified by the nanopattern contributed to the osteogenic differentiation of mBMSCs. The results of our study were consistent with many previous studies, which have shown that nanodots on the surface of bone repair scaffolds promotes stem cell differentiation into osteoblasts through upregulating the osteogenesis-related gene and protein expression levels. The underlying mechanisms may be that the nanodots can activate the Wnt signaling pathway inside cells, which regulated the formation of primary cilium when cells grown on nanodots structure, and regulated the intracellular actin–myosin tension, which in turn modulates the osteogenic differentiation process of cells. Therefore, the nanopattern structures fabricated by our method could be promising topography to enhance bone regeneration, which can be used to fabricate patterns on the surface of bone repair scaffold. However, at present, the application of surface topologies in the field of bone repair is only limited to in vitro cell biology and in vivo animal experimental studies.…”
Section: Resultssupporting
confidence: 89%
“…Studies have shown that bone marrow mesenchymal stem cells (BMSCs), as the main source of osteoblasts in humans, have multi-directional differentiation potential and can differentiate into osteoblasts, chondrocytes and adipocytes under certain conditions. Therefore, BMSCs play a very important role in the treatment of OP (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Induction heating treatment (IHT) has attracted more attention to produce oxide coating on titanium, due to its fast heating, reduced heat loss, cleanness and environmental safety [15]. During IHT process, due to the skin effect of current, the temperature of the surface increases rapidly, while the temperature of the inner part rises at a much lower rate [16]. As a result, a layer of titanium oxide coating forms rapidly on the surface while the intrinsic mechanical properties of the substrate remain constant.…”
Section: Introductionmentioning
confidence: 99%
“…Fomin et al [18,19] preliminarily prepared titanium dioxide coatings with nanocrystalline structure by IHT and demonstrated the improved biocompatibility of the involved medical titanium. Li et al [16,20] also reported the use of IHT to produce titanium dioxide coatings with a micro-and nano-crystalline structure and the improved hydroxyapatite (HA) deposition in simulated body fluid (SBF). We would like to note that, special attention is paid to the enhancement of osteointegration process by improving the morphology and geometrical characteristics, which depend primarily on the duration and temperature in the above-mentioned IHT process.…”
Section: Introductionmentioning
confidence: 99%